PENENTUAN KADAR PROTEIN PADA SUSU KEDELAI (Glycinemax L. Merril) DENGAN MENGGUNAKAN METODE Kjeldahl - Siti Nurbaya; Supartiningsih Supartiningsih (Jurnal Farmanesia, 2020)
Soy milk has a combination of nutrients that are almost the same as cow's milk, but soy milk has low cholesterol, gluten, and lactose levels so that soy milk is safe for consumption by people with lactose intolerance, vegetarians, and is also safe for health. Determination of protein content that is most often done is the determination of crude protein which aims to determine the total amount of protein in food ingredients. The most commonly used protein assay method is the Kjeldahlmethod. This study aims to determine the protein content of soy milk packaged in boxes that are made by themselves and sold in traditional markets. The samples used in this study used packaged soy milk, traditional soy milk, and homemade soy milk. The results showed that the protein content of the three samples determined by the Kjeldahlmethod was 3.35±0.0816% traditional soy milk, 2.31±0.3562% box-packed soy milk, and 2.62±0.2495% whole milk. Homemade soybeans. The protein content in box-packed soy milk, homemade soy milk, and traditional soy milk haveeach met the requirements of SNI (1995). The results showed that the protein content of traditional soy milk was greater than that of packaged soy milk and homemade soy milk.